2010
DOI: 10.6026/97320630004310
|View full text |Cite
|
Sign up to set email alerts
|

Interaction modes at protein hetero-dimer interfaces

Abstract: Hetero dimer (different monomers) interfaces are involved in catalysis and regulation through the formation of interface active sites. This is critical in cell and molecular biology events. The physical and chemical factors determining the formation of the interface active sites is often large in numbers. The combined role of interacting features is frequently combinatorial and additive in nature. Therefore, it is important to determine the physical and chemical features of such interactions. A number of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Bahadur et al (2004) used interface area, crystal packing, residue propensities and hydrophobic interaction energy to measure speci ic interfaces (70 protein-protein complexes) and nonspeci ic interfaces (188 monomeric proteins) and observed that the atomic packing is less compact in non-speci ic interfaces in comparison to the speci ic interfaces. Vaishnavi et al (2010) reported that the variation in the size of interacting protein partners to be a signi icant factor in deciding the mode of interaction using 156 heterodimer protein Bahadur et al (2004) used interface area, crystal packing, residue propensities and hydrophobic interaction energy to measure speci ic interfaces (70 proteinprotein complexes) and non-speci ic interfaces (188 monomeric proteins) and observed that the atomic packing is less compact in non-speci ic interfaces in comparison to the speci ic interfaces. Vaishnavi et al (2010) reported that the variation in the size of interacting protein partners to be a signi icant factor in deciding the mode of interaction using 156 heterodimer protein interfaces.…”
Section: Function Of Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Bahadur et al (2004) used interface area, crystal packing, residue propensities and hydrophobic interaction energy to measure speci ic interfaces (70 protein-protein complexes) and nonspeci ic interfaces (188 monomeric proteins) and observed that the atomic packing is less compact in non-speci ic interfaces in comparison to the speci ic interfaces. Vaishnavi et al (2010) reported that the variation in the size of interacting protein partners to be a signi icant factor in deciding the mode of interaction using 156 heterodimer protein Bahadur et al (2004) used interface area, crystal packing, residue propensities and hydrophobic interaction energy to measure speci ic interfaces (70 proteinprotein complexes) and non-speci ic interfaces (188 monomeric proteins) and observed that the atomic packing is less compact in non-speci ic interfaces in comparison to the speci ic interfaces. Vaishnavi et al (2010) reported that the variation in the size of interacting protein partners to be a signi icant factor in deciding the mode of interaction using 156 heterodimer protein interfaces.…”
Section: Function Of Interfacementioning
confidence: 99%
“…Vaishnavi et al (2010) reported that the variation in the size of interacting protein partners to be a signi icant factor in deciding the mode of interaction using 156 heterodimer protein Bahadur et al (2004) used interface area, crystal packing, residue propensities and hydrophobic interaction energy to measure speci ic interfaces (70 proteinprotein complexes) and non-speci ic interfaces (188 monomeric proteins) and observed that the atomic packing is less compact in non-speci ic interfaces in comparison to the speci ic interfaces. Vaishnavi et al (2010) reported that the variation in the size of interacting protein partners to be a signi icant factor in deciding the mode of interaction using 156 heterodimer protein interfaces. Conte et al (1999) analyzed 75 protein-protein interfaces with known structure and observed small interfaces with small conformational changes and large interfaces with large conformational changes and also reported that some interfaces are predominantly polar and some are non-polar with charged residues above average.…”
Section: Function Of Interfacementioning
confidence: 99%
“…This specificity and accuracy of the interacting proteins determines the fate of cells [1][2][3]. Proteinprotein interactions (PPIs) form the very basis for all biological processes, such as signal transduction, material /energy transport, metabolic reactions, regulation of gene expression, cellular growth and proliferation [3][4][5][6]. These interactions form the fundamentals of the intracellular / intercellular communications [7].…”
Section: Introductionmentioning
confidence: 99%
“…protein size, interface size, interface area, gap volume, gap index, planarity, hydrogen bonds, salt bridges, residue propensity, etc.) based on mean statistics for large datasets [ 8 , 9 , 10 , 11 , 12 , 13 ]. Online web servers are also available for studying PPI using these features [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%